AIR POLLUTION IN TASHKENT CITY: PROBLEMS AND SOLUTIONS (American Journal of Research in Humanities and Social Sciences, 2024)
The 21st century is a period of accelerated urbanization processes on a global scale, and along with socio-economic growth in large cities, environmental problems are also sharply increasing. Tashkent is no exception to this process.[1] Currently, the level of urban air pollution is becoming a serious threat to the health and quality of life of the population.[2]